(untitled) - Waibel, Gabi (Bonn, 2010)
This paper provides a brief overview on the historical development of water resources management in Northern and Southern Vietnam, in order to identify the roots of the current system. It then focuses on state management institutions in the water sector, mapping out the administrative apparatus and legal framework in order to understand how state management in the water sector is organised and practically works. Accordingly, national policies as well as its implementation in practices are examined. The paper concludes on the existing challenges for water resources management and indicates that the nation´s overall pro economic growth aspirations still dominate over environmental concerns.
Keywords: Water-supply,Cung cấp nguồn nước; Managemt,Quản lý; Vietnam,Việt Nam